Mental Health Awareness and Access to Services in Postpartum Women - Shridhar Rawal (Journal of Pharmacy and Bioallied Sciences)
Background: Mental health disorders are prevalent among postpartum women, impacting both maternal and infant well-being. Despite the recognized importance of mental health support during the postpartum period, access to services remains limited for many. Materials and Methods: A cross-sectional survey was conducted with 200 postpartum women within six months postpartum at two major healthcare centers. Participants completed a questionnaire assessing their awareness of mental health issues, access to services, and perceived barriers. Data analysis included descriptive statistics and regression models to determine factors associated with awareness and access levels. Results: Of the 200 participants, 72% reported awareness of postpartum mental health issues, yet only 40% accessed available mental health services. Primary barriers included lack of information (45%), stigma (30%), and financial constraints (25%). Women with higher educational levels showed a significantly greater likelihood of accessing services (P < 0.05), and those with family support were more likely to report positive mental health outcomes. Conclusion: While awareness of postpartum mental health is relatively high, access to services remains a significant challenge, hindered by stigma, lack of information, and financial barriers. Targeted interventions to improve information dissemination and reduce stigma could enhance service accessibility and mental health outcomes for postpartum women.